TEMPERATURE RISE CHARACTERISTICS OF LITHIUM-ION BATTERY CELLS: NUMERICAL SIMULATION AND EXPERIMENTAL ANALYSIS - Dwianto Widyantara, Robby
Lithium-ion batteries in electric vehicles have an optimal temperature range of 25°C – 40°C. Operation outside the optimal temperature can cause a decrease in performance, shorten battery life, and potentially causing thermal runaway. An understanding of battery temperature characteristics and an accurate numerical model is needed to design a Battery Thermal Management System (BTMS) with the right cooling capacity. This study aims to determine the characteristics of the temperature rise of lithium-ion batteries and develop a battery simulation model under operational conditions. Experiments were carried out to measure the heat flux and temperature of the battery cells at 1C and 0.5C charge and discharge rates. The heat flux data obtained was used as an input for the simulation model using curve fit approximation, while the temperature data was used as a validation parameter. The simulation model consists of a battery shell and air. Based on the validated battery cell simulation model, series and parallel battery array models were created. Experiments measuring the temperature distribution of series and parallel battery arrays were carried out to validate the battery array simulation models. The results showed that the heat flux and temperature of the battery tended to increase during the discharge process and tended to reach a constant value during the charging process. Series connection produces a higher temperature difference between batteries compared to parallel connection and battery position has a significant effect on battery temperature. Higher heat flux and battery temperature rise resulted at higher charge and discharge rates. The battery cell simulation models showed results that successfully represent the battery temperature rise from the experimental process. However, the battery array simulation models showed a drastic increase in temperature at the surface between the batteries. Based on the results, it is recommended that BTMS intensify the cooling for the batteries in the middle of battery pack, vary the cooling intensity in series connection, and optimize the cooling capability of the BTMS to obtain the optimal safety of the discharge process and speed of the charging process. The battery array simulation model is suggested to consider the effect of convection and radiation heat transfer modes to provide more representative results.